Revolution Goes East : Imperial Japan and Soviet Communism - Linkhoeva, Tatiana, 1979-; Project Muse. (Ithaca : Cornell University Press, 2020)
"This book demonstrates how contemporary discussions of the communist revolution, its containment, and the issue of imperialism played a fundamental role in shaping Japan's interwar imperial society and policies"--
Before 1917 -- Revolution and intervention -- The anti-Western revolution -- Anticommunism within -- Anarchism against Bolshevism -- The Japanese Communist Party and the Comintern -- National socialism and Soviet communism
Description based on print version record.
Keywords: POLITICAL SCIENCE / Political Ideologies / Communism, Post-Communism & Socialism; Politics and government; Influence (Literary, artistic, etc.); Diplomatic relations; Communism; POLITICAL SCIENCE -- Political Ideologies -- Communism, Post-Communism & Socialism; Communism -- Japan -- History -- 20th century; Soviet Union; Japan; Japon -- Relations exterieures -- URSS; URSS -- Relations exterieures -- Japon; URSS -- Histoire -- 1917-1921 (Revolution) -- Influence; Japon -- Politique et gouvernement -- 1912-1945.; Japan -- Foreign relations -- Soviet Union; Soviet Union -- Foreign relations -- Japan; Soviet Union -- History -- Revolution, 1917-1921 -- Influence; Japan -- Politics and government -- 1912-1945.; History; Electronic books